2017
DOI: 10.1111/imm.12794
|View full text |Cite
|
Sign up to set email alerts
|

Predict disease progression from T‐cell phenotypes in northern pig‐tailed macaques (Macaca leonina) during SIVmac239 infection

Abstract: Macaca leonina (northern pig-tailed macaques, NPMs) have variable disease progression during SIVmac239 infection. In the present study, we analysed, for the first time, the correlations between T-cell phenotypes and disease progression in NPMs during SIVmac239 infection. In comparison to normal progressors (NPs), slow progressors (SPs) had lower chronic T-cell activation and exhaustion levels. In addition, SPs showed higher peripheral CD4 T-cell count and CD4 : CD8 ratio, and lower plasma viral load than NPs. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 33 publications
0
11
0
Order By: Relevance
“…SPMs have been well demonstrated progress to AIDS more rapidly than rhesus macaques after SIVmac239 infection ( 31 ). However, in our previous studies, we found that NPMs progressed to AIDS much more slowly than rhesus macaques, and maintained superior CD4+ T cell homeostasis during SIVmac239 infection ( 32 , 33 ). These results implied great distinctions in physiological and immunologic responses, as well as genetic background between SPMs and NPMs.…”
Section: Introductionmentioning
confidence: 76%
“…SPMs have been well demonstrated progress to AIDS more rapidly than rhesus macaques after SIVmac239 infection ( 31 ). However, in our previous studies, we found that NPMs progressed to AIDS much more slowly than rhesus macaques, and maintained superior CD4+ T cell homeostasis during SIVmac239 infection ( 32 , 33 ). These results implied great distinctions in physiological and immunologic responses, as well as genetic background between SPMs and NPMs.…”
Section: Introductionmentioning
confidence: 76%
“…Thus, the HIV-1 viral reservoir formed in NPMs is likely to be mediated by different mechanisms than those in elite controllers or patients under HAART treatment. Further improvements of this model as well as a detailed understanding of viral latency mechanisms could be achieved by systemic comparison of LRA efficiencies in NPMs and in human patients, and through inoculation with stHIV-1 recombinants or SIV that have more robust replication capacity in NPMs [51].…”
Section: Discussionmentioning
confidence: 99%
“…As our attention mainly focused on the dynamics of CD4 + T cell, we subsequently analyzed the changes of peripheral T cell during SIVmac239 infection as previously described (Supporting Information Fig. 1) . The results indicated that NPMs had higher T cell and CD4 + T‐cell counts than ChRMs, no matter in acute or chronic phase (Fig.…”
mentioning
confidence: 94%